2015
DOI: 10.1371/journal.pone.0121887
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines Promote Actinobacillus pleuropneumoniae Growth by Regulating Iron Metabolism

Abstract: Catecholamines are host stress hormones that can induce the growth of many bacteria by facilitating iron utilization and/or regulate the expression of virulence genes through specific hormone receptors. Whether these two responsive pathways are interconnected is unknown. In our previous study, it was found that catecholamines can regulate the expression of a great number of genes of Actinobacillus pleuropneumoniae, an important swine respiratory pathogen. However, bacterial growth was not affected by catechola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…A. pleuropneumoniae 4074 (serovar 1) was cultured on tryptic soy agar (TSA) or in tryptic soy broth (TSB; Difco Laboratories, USA) supplemented with 10 g/ml of NAD and 10% (vol/vol) filtered cattle serum at 37°C as described previously (14). The susceptibility of the TG pigs to A. pleuropneumoniae infection was evaluated in two infection studies.…”
Section: Methodsmentioning
confidence: 99%
“…A. pleuropneumoniae 4074 (serovar 1) was cultured on tryptic soy agar (TSA) or in tryptic soy broth (TSB; Difco Laboratories, USA) supplemented with 10 g/ml of NAD and 10% (vol/vol) filtered cattle serum at 37°C as described previously (14). The susceptibility of the TG pigs to A. pleuropneumoniae infection was evaluated in two infection studies.…”
Section: Methodsmentioning
confidence: 99%
“…Iron metabolism is of high importance for the pathogen to survive and multiply in the host. It has been shown recently that catecholamine binding to App facilitates iron uptake, although iron availability is highly decreased during acute infection as a physiological acute reaction during inflammation (Humann‐Ziehank et al., ; Li et al., ). The fact that more than 50 App genes are involved in iron uptake and metabolism (Xu et al., ), some of which are differentially expressed during infection (Deslandes et al., ; Klitgaard, Friis, Jensen, Angen, & Boye, ), supports the major importance of this bacterial adaptation strategy for disease pathogenesis (Bossé et al., ).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…The effect of stress hormones such as catecholamine on virulence factor expression in App has been shown at a molecular level (Li et al., ). In addition, a status of well‐being of pigs in an enriched housing system had an influence on immune parameters and led to a reduction of lung alterations after experimental infection (van Dixhoorn et al., ).…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…For E.coli, Salmonella, and A. pleuropneumoniae, it was found that the stimulation of planktonic growth was independent of QseC since a mutant strain still underwent catecholamine mediated planktonic growth stimulation [57,80,92]. This is consistent with the results of the CAT-Fe mediated planktonic growth stimulation in A. actinomycetemcomitans, which was also independent of a functional QseC.…”
Section: Discussionsupporting
confidence: 81%
“…This stimulation of planktonic growth is independent of a functional QseC [92], but biofilm formation is attenuated for a QseC mutant in the presence of catecholamines [119]. In addition, the stimulation of planktonic growth in E. coli can be blocked by the addition of adrenergic receptor antagonists [80,55].…”
Section: Introductionmentioning
confidence: 97%